If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5y + 1) + -1(-4y + -2) = -7 Reorder the terms: -1(1 + 5y) + -1(-4y + -2) = -7 (1 * -1 + 5y * -1) + -1(-4y + -2) = -7 (-1 + -5y) + -1(-4y + -2) = -7 Reorder the terms: -1 + -5y + -1(-2 + -4y) = -7 -1 + -5y + (-2 * -1 + -4y * -1) = -7 -1 + -5y + (2 + 4y) = -7 Reorder the terms: -1 + 2 + -5y + 4y = -7 Combine like terms: -1 + 2 = 1 1 + -5y + 4y = -7 Combine like terms: -5y + 4y = -1y 1 + -1y = -7 Solving 1 + -1y = -7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1y = -7 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = -7 + -1 -1y = -7 + -1 Combine like terms: -7 + -1 = -8 -1y = -8 Divide each side by '-1'. y = 8 Simplifying y = 8
| 5x+4=6-(3x-3) | | 2-5t^2=4 | | 4x-78=x | | 2x+.2=60 | | 4x+x-6=1 | | m(5-y)-5+y= | | 2x^3-x^2-4x-2=0 | | 3y^2=-12 | | 14(t-4)+4t=6(3t+4)-13 | | 7m^2=-56m | | x^2-24x-21=0 | | 8x^2+8x=-2 | | 3y^2+33y+90=0 | | x-7.1=-3.3 | | n+39=13 | | -5x-6=14 | | y^4+6y^3=7y^2 | | 8x-9y=6 | | x^4-2x^2-15= | | -8*-4= | | -8*4= | | 5y-20=-4y | | 2x^4-50= | | 15a^3b+20a^2b^2-35a^2b= | | -x^2+2x-1= | | 7u=-6 | | 4y^2-18y-70= | | 12x-8=180 | | 9g^2-9g= | | 4x^2-17x+4y^2= | | .2+x=60 | | (5x+3)*(5x+3)=6 |